2023
DOI: 10.1007/s11469-023-01073-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Predictors of Video Game Addiction According to Expertise Levels of the Players: The Role of Time Spent on Video Gaming, Engagement, Positive Gaming Perception, Social Support and Relational Health Indices

Abstract: This study aimed to examine the predictive relationship between video gaming addiction (VGA) and the level of video gaming competency among video gamers. Additionally, the role of time spent playing video games, video game engagement (VGE), video game positive perception (VGPP), social support and quality of relationships with peers were examined. We recruited 227 participants using the purposive sampling method. Of the participants, 50.20% self-identified as Novice-Amateur video gamers while 49.80% indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
5
0
1
Order By: Relevance
“…In Study 1, the inclusion of IGI alongside DGI significantly improved the explanatory power of the model, accounting for more variance in GD risk. However, Study 2 did not replicate this finding, suggesting that the influence of IGI on GD risk may vary across different populations or contexts [see the partially conflicting results quoted above ( 14 , 16 , 17 )]. It is worth noting that in Study 1 the sample was very diverse in age (13–70), and the procedure did not allow for the behavior of the respondents to be controlled when filling out the questionnaire.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In Study 1, the inclusion of IGI alongside DGI significantly improved the explanatory power of the model, accounting for more variance in GD risk. However, Study 2 did not replicate this finding, suggesting that the influence of IGI on GD risk may vary across different populations or contexts [see the partially conflicting results quoted above ( 14 , 16 , 17 )]. It is worth noting that in Study 1 the sample was very diverse in age (13–70), and the procedure did not allow for the behavior of the respondents to be controlled when filling out the questionnaire.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are in line with previous research focused on individual components of IGI: Cabreza-Ramirez et al ( 14 ) showed that a feeling of belonging to the Twitch community (a service mainly focused on video game streaming) plays an important role in the model of pathological game use; Ortiz de Gortari et al showed that intrusive thoughts regarding gaming are correlated with GD ( 16 ). Interestingly, Yildiz Durak et al ( 17 ) showed that time spent watching gaming videos on Twitch is correlated with GD, whereas time spent watching gaming streams on unspecified platforms or gaming itself is not linked to GD. Thus, our research fits into a relatively new direction of research that verifies the role of individual behaviors indirectly related to gaming in the context of GD risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Πέραν των γνωστικών και συμπεριφορικών παρεμβάσεων που συνήθως χρησιμοποιούνται για την ενίσχυση των ικανοτήτων είναι σημαντικό να υιοθετηθούν και παρεμβάσεις οι οποίες θα λαμβάνουν υπόψιν τους το νευρολογικό υπόβαθρο των ατόμων που κρίνονται επιρρεπή στην εμφάνιση διαταραχών που σχετίζονται με την προβληματική χρήση του διαδικτύου και των βίαιων ηλεκτρονικών παιχνιδιών. Επιπροσθέτως, αναφορικά με τη μακροπρόθεσμη διαχείριση της κατάθλιψης, προτείνεται ο σχεδιασμός παρεμβάσεων για τη μείωση της εξάρτησης (Gong et al, 2021˙ Moge & Romano, 2020) και της προβληματικής ενασχόλησης με τα εν λόγω παιχνίδια (Yildiz Durak et al, 2023) και μάλιστα μέσω της χρήσης ειδικά σχεδιασμένων ηλεκτρονικών παιχνιδιών (π.χ., SPARX, Dance Central, Plants vs Zombies) με τεκμηριωμένα θεραπευτικά οφέλη (Ruiz et al, 2022˙ Russoniello et al, 2019. Τέλος, σε περίπτωση εφήβων οι οποίοι εμφανίζουν εξάρτηση από το διαδίκτυο ή Διαταραχή Διαδικτυακού Παιχνιδιού είναι χρήσιμο να διερευνηθεί θεωρητικά αλλά και πρακτικά η ενδεχόμενη αποτελεσματικότητα μιας ομαδικής θεραπείας καθώς και η σύγκριση των αποτελεσμάτων της ομαδικής θεραπείας με αυτά της ατομικής θεραπείας.…”
Section: περιορισμοί-προτάσειςunclassified